Openness and Warmth in the Digital World: Examining Therapeutic Relationships in Online Counseling in Javanese Culture - Fajar Rosyidi; Niken Dwi Saputri; Esthi Mursithi; Novian Uticha Sally (State Islamic University (UIN) Salatiga, 2024)
The advancement of digital technology has significantly transformed counseling practices, including those in Indonesia. This study explores the therapeutic relationships in online counseling, particularly as the cultural values of togetherness and openness characteristic of Javanese society influence them. A qualitative approach, employing a phenomenological study design, was utilized for this research. The subjects included 15 participants, comprising eight counselors and seven clients, selected through purposive sampling techniques. Data collection involved in-depth interviews, non-participant observation, and documentation. Techniques such as data triangulation and member checking were employed to ensure data validity. The findings reveal that while non-verbal communication barriers and limited personal interaction pose challenges, digital counseling expands access to services. Interestingly, in some cases, clients exhibit greater openness, benefiting from the anonymity and physical distance that digital platforms provide. This study emphasizes the significance of adopting a culturally informed counseling approach to enhance the quality of therapeutic relationships in the digital era.